2021
DOI: 10.1080/15563650.2021.1894333
|View full text |Cite|
|
Sign up to set email alerts
|

Nine prohibited stimulants found in sports and weight loss supplements: deterenol, phenpromethamine (Vonedrine), oxilofrine, octodrine, beta-methylphenylethylamine (BMPEA), 1,3-dimethylamylamine (1,3-DMAA), 1,4-dimethylamylamine (1,4-DMAA), 1,3-dimethylbutylamine (1,3-DMBA) and higenamine

Abstract: Background: Weight loss and sports supplements containing deterenol have been associated with serious adverse events including cardiac arrest. Objective: To determine the presence and quantity of experimental stimulants in dietary supplements labeled as containing deterenol sold in the United States. Methods: Dietary supplements available for sale in the US and labeled as containing deterenol or one of its synonyms (e.g., isopropylnorsynephrine and isopropyloctopamine) were purchased online. For each brand, on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 26 publications
0
24
0
Order By: Relevance
“…Notwithstanding efforts to increase supplement safety via the FDA introduction of the Dietary Supplement Health and Education Act of 1994 (DSHEA)—most supplements are sold without a prescription, meaning that consumers may make purchases without adequate counselling (Nutrition C for FS and A, 2020). Additionally, in opposition to FDA recommendations, a more recent study revealed a concerning fact that 17 US-branded sports and weight loss supplements contained 9 FDA-prohibited stimulants (Cohen et al, 2021). These include deterenol, beta adrenergic agonist, which induce serious side effects such as respiratory distress and hypotension.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notwithstanding efforts to increase supplement safety via the FDA introduction of the Dietary Supplement Health and Education Act of 1994 (DSHEA)—most supplements are sold without a prescription, meaning that consumers may make purchases without adequate counselling (Nutrition C for FS and A, 2020). Additionally, in opposition to FDA recommendations, a more recent study revealed a concerning fact that 17 US-branded sports and weight loss supplements contained 9 FDA-prohibited stimulants (Cohen et al, 2021). These include deterenol, beta adrenergic agonist, which induce serious side effects such as respiratory distress and hypotension.…”
Section: Discussionmentioning
confidence: 99%
“…As a result of these incidents, coupled with a lack of safety data, the FDA issued a warning to manufacturers and distributors in 2012 in order to halt DMAA sales; now, DMAA is no longer an option for patients who could otherwise benefit from its lipolytic effects (Bloomer et al, 2018). However, despite deaths and subsequent prohibition, a recent study showed that 17 fitness or weight loss supplements currently on the market contain DMAA in their formulation (Cohen et al, 2021).…”
Section: Clarification Of the Effects Of Different Supplementsmentioning
confidence: 99%
“…The positional isomer of amphetamine, BMPEA, is currently uncontrolled, whereas amphetamine is a controlled substance. BMPEA can also be found in nutritional supplements for athletes and dieters [5][6][7]. Because of their positional isomers, their similar mass spectra can lead to incorrect identification [8].…”
Section: Introductionmentioning
confidence: 99%
“…Considerable labeling inconsistencies are reported in the literature with respect to the analysis of dietary supplements 19–21 . Regarding PWS, there are three major issues: the contamination with undeclared substances; the presence of stimulants that are declared on label but are not approved by the regulatory agencies; and inaccurate caffeine values 22–24 . In fact, the inaccurately labeling problem is not specific to caffeine but rather reflects a broader problem regarding the quantity of stimulants found in PWS, including other substances, such as small components of botanicals (e.g., yohimbine and higenamine) 25,26 …”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21] Regarding PWS, there are three major issues: the contamination with undeclared substances; the presence of stimulants that are declared on label but are not approved by the regulatory agencies; and inaccurate caffeine values. [22][23][24] In fact, the inaccurately labeling problem is not specific to caffeine but rather reflects a broader problem regarding the quantity of stimulants found in PWS, including other substances, such as small components of botanicals (e.g., yohimbine and higenamine). 25,26 Studies that quantified caffeine in supplements reported numerous irregularities, including products without statement of the caffeine content, intra-and inter-lot variations of caffeine content, or even the absence of this compound.…”
mentioning
confidence: 99%